1985
DOI: 10.1093/infdis/152.5.887
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Shock and Hemorrhage in a Fulminating Viral Infection (Ebola)

Abstract: Eleven rhesus monkeys were monitored intensively during experimental infection with Ebola virus. Prominent neutrophilia with left shift and lymphopenia were the earliest abnormalities and were statistically significant by day 4 (P less than .02 and P less than .01, respectively). By day 4 falls in platelet counts were not statistically significant, whereas in vitro platelet aggregation was markedly depressed, progressing rapidly to complete failure by the time of maximum illness. Intraplatelet protein studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(92 citation statements)
references
References 20 publications
5
85
0
2
Order By: Relevance
“…Results from many studies have shown biochemical and histological evidence of disseminated intravascular coagulation in both experimentally infected NHPs and humans 19,20,22,23,40,[44][45][46][49][50][51]53,54,70,[73][74][75][76][77][78][79] . The mechanisms that cause these coagulation disorders are not fully understood, but the expression or release of tissue factor from filovirus-infected monocytes and macro phages seems to play a role 54,55 .…”
Section: Box 1 | Animal Modelsmentioning
confidence: 99%
“…Results from many studies have shown biochemical and histological evidence of disseminated intravascular coagulation in both experimentally infected NHPs and humans 19,20,22,23,40,[44][45][46][49][50][51]53,54,70,[73][74][75][76][77][78][79] . The mechanisms that cause these coagulation disorders are not fully understood, but the expression or release of tissue factor from filovirus-infected monocytes and macro phages seems to play a role 54,55 .…”
Section: Box 1 | Animal Modelsmentioning
confidence: 99%
“…The ribonucleoprotein (RNP) complex that mediates transcription and replication of the viral genome comprises 4 of these proteins: nucleoprotein (NP), VP35, VP30, and the RNA-dependent RNA polymerase (L). The 3 other proteins-glycoprotein (GP), VP40, and VP24-are membrane-associated proteins [5].…”
Section: E Zaire Ebolavirus (Ebov)mentioning
confidence: 99%
“…Pretreating rhesus monkeys with antioxidants, such as vitamin E, failed to confer any beneficial or protective effect to ZEBOV-infected rhesus monkeys (Ref. 64). …”
Section: Regulation Of the Pro-inflammatory Responsementioning
confidence: 99%